Molecular footprint and pathways of DOM biotransformation in the Yangtze River - Guangrui Yang; Farong Chen; Songchol Kang; Jiaming Chen; Chu Zhao; Lize Meng; Xinyi Zhang; Jiayue Lu; Shuaidong Li; Zihao Bian; Jian Zhou; Qihao Jiang; et al. (Water Research, 2026)

Amplification-free electrochemiluminescence biosensors based on peptide-templated gold nanocluster and CRISPR-Cas12a for Mycobacterium tuberculosis IS6110 detection - Lingjun Cheng; Qingmei Yang; Yuanyuan Yang; Yufeng Wang; Qingfei He; Zhiyan Zou; Canping Su; Jiaming Chen; Yinhuan Liu; Guolin Hong (Analytica Chimica Acta, 2026)

Amphibian skin peptides: Diversity, biological functions, and research progress - Zihui Chen; Qing Pan; Jiaming Zhang; Ren Lai; Wenhua Yu; Aili Wang (Toxicon, 2026)

Time-resolved volatile profiles and molecular-species lipid remodeling during lipase treatment of anhydrous milk fat - Anqi Chen; Qingyun Xu; Jiaming Li; Yanxi Chen; Qiance Shen; Guocheng Du; Jianghua Li; Jian Chen (Food Research International, 2026)

Engineering antimicrobial and anti-photooxidative films via a cyclodextrin metal-organic frameworks encapsulation strategy for Mongolian cheese preservation - Liying Yang; Long Chen; Jiaming Deng; Douxin Xiao; Wenyan Zhao; Alideertu Dong (Food Research International, 2026)

LvBlimp1 and LvHes1 coregulate the function of macrophage-like phagocytes in shrimp hemolymph - Jiaming Liu; Yaohui Chen; Wenyong Jiang; Zhiyao Lu; Nuo Lin; Qingyun Liu; Xiuli Chen; Yongzhen Zhao; Fan Wang (Fish & Shellfish Immunology, 2026)

A multifunctional photothermal nanoplatform integrating CD47 degradation and metabolic reprogramming for potentiated tumor immunotherapy - Jiaming Zhang; Chao Chen; Zhousheng Lin; Zeyu Liu; Juan Zhang; Jieying Qian; Xiaowan Huang; Yunjiao Zhang; Guangyu Yao (Chemical Engineering Journal, 2026)

Microalgae-based biogas slurry treatment integrated with sustainable aviation fuel production: from waste to high-value bio-jet fuel - Binbin Zhu; Hongyin Chen; Jing Lv; Wenjun Zhang; Jiaming Liu; Ruirui Liu; Bishu Qi; Shuhui Li; Chengyu Yang; Xiao Yan; Zijian Xia; Xingliang Xu; et al. (Bioresource Technology, 2026)

Potential of individual-scale phenological measurements for improving wood productivity and maintaining genetic diversity in forest management - Haruka Sano; Tai-Shen Chen; Jiaming Yan; Naoko Miura; Minoru Inamori; Wei Guo; Sachiko Isobe; Kazutaka Kusunoki; Hiroyoshi Iwata (Forest Ecology and Management, 2026)

Strain-specific fermentation reshapes aroma-active volatiles and antioxidant-related properties of soy protein isolate-based plant milk - Hanhan Shi; Jiaming Li; Tanxu Tang; Tianzhi Qu; Jian Chen; Anqi Chen; Jianghua Li (Food Bioscience, 2026)

Nanoconfined humic acid-supported nZVI enhances imidacloprid remediation without compromising soil microbiome or exacerbating ARG health risks - Na Li; Jiaming Yi; Lin Zhu; Du Chen; Meizhen Wang; Dan Huang (Environmental Research, 2026)

Electrochemically crosslinked poly(arylene ether sulfone)-triphenylamine electrochromic polymer networks for smart windows - Keying Feng; Zhen Xing; Xiangfu Shi; Jiaming Tian; Hao Zhang; Zong-Quan Wu; Zheng Chen; Zhenhua Jiang (Chemical Engineering Journal, 2026)

Pixel relationship-constrained weakly supervised semantic segmentation for remote sensing images: enhancing CAM integrity and pseudo-label quality - Jiaming Fan; Dali Chen; Yang Liu; Shixin Liu (International Journal of Remote Sensing, 2026)

Effects of renewable portfolio standards obligation distribution: Equilibrium analysis of supply side vs. demand side in power supply chain networks - Huan Zhang; Jiaming Wu; Sien Chen; Jianli Jiang (Utilities Policy, 2026)

High resolution river and estuarine water level topography from nadir altimetry - Luciana Fenoglio; Jiaming Chen; Stefano Vignudelli; Ron Abileah; Elena Zakharova; Marco Restano; Jerome Benveniste; Jürgen Kusche (Journal of Hydrology, 2026)

Auxiliary fermentation with Pediococcus acidilactici C1 reshapes flavor formation in sufu: An integrated metagenomic, flavoromic and non-targeted metabolomic deciphering - Chen Chen; Jiaming Li; Feng Wang; Mei Cheng; Tao Sheng; Zahoor Ahmed; Jingwei Hu; Yibin Zhou (Food Chemistry, 2026)

Defined co-fermentation of Kluyveromyces marxianus and lactic acid bacteria enhances bioactivity and aroma formation in black tea kombucha - Aiping Yao; Jiaming Li; Yuanyuan Zhao; Tianzhi Qu; Yan Geng; Lingxi Zhou; Anqi Chen; Jian Chen (Food Bioscience, 2026)

Bioenrichment of conjugated linoleic acid in oil-in-water (O/W) emulsion by Niubie as a natural biocatalyst - Yusen Wu; Xiaobi Yang; Na Liu; You Chen; Jiaming Gu; Likang Qin; Song Miao (Food Bioscience, 2026)

Polyphase of uranium mineralization in granite-related deposits: Insights from the geochronology and geochemistry of pitchblende and coffinite in the Xiwang uranium deposit, South China - Bin Liu; Weifeng Chen; Haidong Li; Jiaming Qi; Liang Qiu; Hongfei Ling (Applied Geochemistry, 2026)

Explicit wave height prediction model and regularity analysis for floating breakwaters based on deep symbolic regression - Jiaming Jing; Xiaofei Cheng; Haibo Chen; Wei Xie (Frontiers in Marine Science, 2026)
The accurate prediction of wave attenuation across floating breakwaters is essential for coastal structure design and nearshore aquaculture safety. This study employs Physical Symbolic Optimization (PhySO) to model the transmission of significant wave height (H s ) and maximum wave height (H max ) behind a floating breakwater in Lianjiang, Fujian Province. Using in-situ wave data including incident wave height, period, and direction, the dataset is split into 80% training and 20% testing sets, with constraints on expression complexity and physical consistency. Results show that PhySO produces explicit, interpretable formulas with strong generalization ability: the best H max expression achieves accuracy comparable to black-box machine learning models, while H s expressions show slightly lower but still reliable performance. Simple linear scaling expressions exhibit excellent robustness across all wave conditions, and incident wave height is confirmed as the dominant controlling factor. This work demonstrates the value of PhySO in balancing accuracy and physical interpretability, offering a practical and easy-to-use tool for engineering applications.

Study on the synergistic melting combustion characteristics of municipal solid waste incineration fly ash and circulating fluidized bed gasification fly ash - Wei Li; Jiaming Chen; Shaobo Yang; Qiangqiang Ren (Fuel, 2026)

A significantly enhanced Cu+/Cu0 catalytic active structure via the electronic effect of K for methyl glycolate synthesis - Xiaoxiao Zheng; Jiaming Wang; Peipei Lei; Qihong Xue; Xian Kan; Jiangang Chen (Chemical Engineering Journal, 2026)

Contrasting Resource-Use Strategies Under Tropical Stress: Linking Leaf Functional Traits to Fruit Biomass and Oil Yield in Camellia Oleifera - Wenjun Hong; Jindian Yang; Shufen He; Jiaming Song; Weiyu Chen; Zhitong Mai; Feifei Chen; Ling Lin; Chuanteng Huang (Tropical Plant Biology, 2026)

Fully coupled numerical model of moored structures-mooring line-ice ridge interaction - Jiaming Chen; Shengjie Rui; Sen Han; Shifeng Ding; Jie Tan; Li Zhou (Ocean Engineering, 2026)

Assessment of laterization degree of tropical residual laterites overlying carbonate rocks in Yunnan, China - Haiyan Gao; Zhongxin Deng; Zemin Xu; Yixi Wen; Jiaming Zhang; Jipu Chen; Lin Tian (CATENA, 2026)

Petrogenesis of Yanshanian granites in the Guidong complex, Northern Guangdong: Implications for uranium mineralization - Haiyang Wang; Changqian Ma; Jiayong Pan; Fujun Zhong; Fei Xia; Xiangping Gu; Guanghua Liu; Zhengle Chen; Jungang Liu; Jiaming Qi (Acta Geochimica, 2026)

Mass and Energy Balance-Oriented Allocation Mechanism for Petrochemical Product Carbon Footprint - Lili Sun; Hongju Chen; Hetian Zhu; Xiaotong Li; Jiaming Gu; Yinghui Han; Guofei Shen; Yunhu Gao; Baojuan Dou; Chong Wei; Qun Shen; Wei Wei (Aerosol Science and Engineering, 2026)

Corrigendum to “Influence of altered volcanic ash on lithium enrichment in Late Carboniferous coals in Odors Basin, North China: Insights from LA-ICP-MS and lithium isotope data” [Int. J. Coal Geol. 320 (2026) 104999] - Jiaming Zhang; Zhibo Zhang; Yinghai Guo; Difei Zhao; Yilin Chen; Zhuoxi Liu (International Journal of Coal Geology, 2026)

Influence of altered volcanic ash on lithium enrichment in Late Carboniferous coals in Odors Basin, North China: Insights from LA-ICP-MS and lithium isotope data - Jiaming Zhang; Zhibo Zhang; Yinghai Guo; Difei Zhao; Yilin Chen; Zhuoxi Liu (International Journal of Coal Geology, 2026)

Research on the Support Mechanism of Tunnel Anchor Bolt Based on Physical Model Experiments and Continuous–Discontinuous Theory - Mingyi Wang; Shaobo Chai; Bo Hu; Chen Xu; Jiaming Wu; Yongqiang Zhou; Xiaodong Fu (Rock Mechanics and Rock Engineering, 2026)

Development of an indirect ELISA and an immunochromatographic test method for early detection of Haemonchus contortus infection in sheep - Xueqiu Chen; Lingyun Mou; Manqin Deng; Jingju Zhang; Jiaming Yu; Jianfang Li; Hongli Zhang; Guangxu Ma; Yi Yang; Aifang Du (Veterinary Parasitology, 2026)

The dual roles of dissolved organic matter as a source and sink of hydroxyl radicals in the photodegradation of carbamazepine in liquid water and ice - Caihong Jiang; Jiaming Chen; Meng Yuan; Shuang Xue; Yingzi Lin; Yingtan Yu (Process Safety and Environmental Protection, 2026)

Optimization design research of vibration control parameters for Submerged Floating Tunnel based on GA-AIF-PSO algorithm - Jiaming Xie; Jianyun Chen; Ning Su; Jing Li; Qiang Xu (Ocean Engineering, 2026)

Aerodynamic and wake characteristic analysis of a dual-rotor wind turbine under surge motion based on modified actuator line model - Mengshang Zhao; Kai Wang; Siqi Chen; Jiaming Liu; Yuan Li (Ocean Engineering, 2026)

High turbidity induced by extreme precipitation complicates the relationships between molecular and optical properties of DOM in the Yangtze River - Yue Ren; Guangrui Yang; Jiale Jin; Chu Zhao; Zhishan Ye; Jiaming Chen; Xinyi Zhang; Tao Huang; Changchun Huang (Journal of Water Process Engineering, 2026)

Cerium-modified Cu-SSZ-13 catalysts: Enhanced low-temperature activity and hydrothermal stability for efficient NOx reduction - Bin Guan; Kaiyou Shu; Lei Zhu; Tiankui Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Hongtao Dang; Luyang Zhang; et al. (Journal of Environmental Chemical Engineering, 2026)

Multi-membrane integrated process enables efficient electrodialytic separation of alkaloids from aqueous extract of Caulis sinomenii - Lanlan Zhang; Xixi Ma; Tingting Xu; Shanshan Liu; Luna Chen; Jiaming Ji; Jinfeng He; Li Sun; Xiaocheng Lin; Chuanrun Li; Haiyang Yan (Desalination, 2026)

BnaCIPK9 homoeologs mediate the dosage-dependent regulation of seed oil in allotetraploid Brassica napus L - Nan Wang; Jingquan Tang; Xianfei Hou; Chengtao Quan; Jiaming Mai; Chao He; Rundong Chen; Baolong Tao; yuanguo Gu; Donghai Jia; Tingdong Fu; Jitao Zou; et al. (Theoretical and Applied Genetics, 2026)

Transport modeling of ZVI-AC mixtures in Cr(VI) remediation driven by spectral induced polarization - Xinmin Ma; Alexis Maineult; Jiaming Zhang; Chen Chao; Ruijue Zhao; Jian Meng; Yaxun Wang; Deqiang Mao (Journal of Hazardous Materials, 2026)

Research on emission control performance of SSCR system based on multi-condition operation and three-high tests - Bin Guan; Kaiyou Shu; Lei Zhu; Tiankui Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Hongtao Dang; Luyang Zhang; et al. (Fuel, 2026)

Environmental exposure to bisphenol S suppresses white adipocyte beiging and energy expenditure via CYP2E1 in mice - Qi Liu; Yuancheng Shao; Jiaming Xue; Yicheng Jiang; Shuai Chen; Dongmei Wang; Yan Zhou; Jie Zhao; Wei Gao; Liming Tang (Environmental Pollution, 2026)

Uniaxial compressive behavior of frozen silty clay at extreme low temperature with varying initial water content - Jiaming Xian; Wansheng Pei; Yuanming Lai; Mingyi Zhang; Fan Yu; Yanyan Chen (Cold Regions Science and Technology, 2026)

Hybrid framework combining machine learning with mechanism models for enhanced forecasting of biomass gasification products - Jiaming Song; Zongqi Chen; Haining Tang; Hong Ding; Shiliang Wu; Zhou Liu; Feng Gong (Bioresource Technology, 2026)

Non-uniform salinity combined with localized nitrogen supply improves water use efficiency and fruit visual and storage qualities in tomato - Jinjing Liu; Zhenchang Wang; Yongfeng Huang; Yuexiong Wang; Weixing Wen; Kexin Chen; Yanmin Bi; Yating He; Jiaming You; Yaosheng Wang (Plant and Soil, 2026)

Modern pollen analysis on peatlands across monsoonal China and its implications for reconstruction - Shu Chen; Mengmeng Wang; Chunmei Ma; Tianyi Tang; Rui Ke; Jiaming Hou; Xinrong Zhang; Zhuo Zheng; Xiayun Xiao; Yan Zhao; Huayu Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Determining the age of Guadalupian extinction by in situ uranium–lead geochronology in regard to middle Permian giant bivalve Alatoconchidae fossils in the Northwest margin of the South China Plate - Xueqin Zhao; Ran Liu; Fudong Wang; Qian Li; Chen Su; Jiaming Ding; Caifu Xiong; Wentao Li; Jianhua Zhang; Keli Hou (Gondwana Research, 2026)

The role of ammonia in the global energy transition: opportunities and challenges in ammonia gas turbine technology - Shuai Chen; Bin Guan; Lei Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Kaiyou Shu; Hongtao Dang; Luyang Zhang; et al. (Fuel, 2026)

High-efficiency catalytic removal of N2O from ammonia-fueled engine exhaust - Bin Guan; Zhongqi Zhuang; Lei Zhu; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Kaiyou Shu; Hongtao Dang; Luyang Zhang; Tiankui Zhu; et al. (Fuel, 2026)

Synergistic effect in dual-site catalyst with silanol-stabilized Co2+-bonded Ni clusters for methane dry reforming - Zijun Huang; Dedong He; Han Xiao; Jun Liang; Jiaming Dong; Zhenzhong Tao; Xiaohua Cao; Dingkai Chen; Yongming Luo (Chemical Engineering Journal, 2026)

Synergistic layer engineering for high-efficiency blue emission in pure-bromide quasi-2D perovskite light-emitting diodes - Jiaming Yu; Bochao Jia; Shuguang Zhang; Yachun Guo; Yue Liang; Jiangshan Chen; Linfeng Lan; Junbiao Peng (Chemical Engineering Journal, 2026)

Pipeline Systems in Floating Offshore Production Systems: Hydrodynamics, Corrosion, Design and Maintenance - Jin Yan; Yining Zhang; Zehan Chen; Pengji Li; Yuting Li; Zeyu Cao; Jiaming Wu; Kefan Yang; Dapeng Zhang (Journal of Marine Science and Engineering, 2026)
Floating offshore production systems play a critical role in offshore resource development, where the structural integrity and operational safety of risers, umbilical cables, and mooring cables are of paramount importance. Focusing on the failure risks of these key components under harsh marine environments, this paper systematically reviews the coupled mechanisms of wave-induced loading, electrochemical corrosion, and material fatigue. Unlike traditional reviews on offshore pipelines and cables, this study not only examines the mechanical performance of deepwater pipelines and cables along with representative research cases but also discusses corrosion mechanisms in marine environments and corresponding repair and mitigation strategies. In addition, recent advances in machine learning-based digital twin frameworks and real-time monitoring technologies are reviewed, with an analysis of representative application cases. The findings indicate that interdisciplinary material innovations combined with data-driven predictive models are essential for addressing maintenance challenges under extreme ocean conditions. Furthermore, this review identifies existing research gaps in data fusion for monitoring technologies and outlines clear directions for the intelligent operation and maintenance of future deep-sea infrastructure.

Heterogeneous distribution of salinity and nitrogen in the root-zone influence nitrogen harvest index and natural 15N abundance of tomato - Jinjing Liu; Zhenchang Wang; Yuexiong Wang; Yaosheng Wang; Yousef Alhaj Hamoud; Cheng Hong; Hiba Shaghaleh; Rangjian Qiu; Jiaming You; Minghao Tian; Kexin Chen; Xiaoman Qiang; et al. (Plant Science, 2026)

Changes in photo-reactivity and optical properties of dissolved organic matter during the freezing process of water - Man Yang; Jiaming Chen; Meng Yuan; Shuang Xue; Zhaohong Zhang (Journal of Environmental Management, 2026)

Integrated network toxicology, molecular docking and transcriptomics reveal the mechanistic role of phthalate esters in metabolic disease pathogenesis - Yuancheng Shao; Qi Liu; Yicheng Jiang; Gang Zhou; Xihan Gu; Shufan Zhang; Shuai Chen; Jiaming Xue; Liming Tang (Food and Chemical Toxicology, 2026)

Extreme precipitation amplified the cumulative effects of DOM availability on organic-sourced DIC in the Yangtze River - Chu Zhao; Guangrui Yang; Lize Meng; Heran Chen; Shuaidong Li; Farong Chen; Zihao Bian; Jiaming Chen; Jian Zhou; Qihao Jiang; Tao Huang; Hao Yang; et al. (Water Research, 2025)

Synergizing machine learning and interpolation methods: A Stacking framework for global-scale satellite soil moisture gap filling - Jiaming Rong; Jiangyuan Zeng; Kun-Shan Chen; Hongliang Ma; Pengfei Shi; Husi Letu; Xiang Zhang; Xihui Gu; Haiyun Bi; Chunlin Zhang (Remote Sensing of Environment, 2025)

Reshaping spatial–temporal pattern of suspended sediment concentration in the Yangtze River mainstem by damming reservoirs based on nearly 40 years Landsat observations - Farong Chen; Guangrui Yang; Yanhui Dai; Jiale Jin; Chu Zhao; Zhishan Ye; Jiaming Chen; Xinyi Zhang; Tao Huang; Changchun Huang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Spatiotemporal changes in global cropland fire activity from 2003 to 2020 - Jiaming Wang; Xiaoting Zhong; Jie Zhao; Xiaofan Shen; Mengyu Wang; Junhao He; Xiaohan Meng; Qiuling Chen; Xinrui Lu; Liang Wang; Chao Yue (Global and Planetary Change, 2025)

Advancing kombucha fermentation: Microbial interactions, functional metabolites, and innovative optimization strategies - Anqi Chen; Jiaming Li; Aiping Yao; Guocheng Du; Jianghua Li; Jian Chen (Food Chemistry, 2025)

Flexible CeO₂ surface engineering optimizes atomically dispersed Ru catalyst-support interaction for enhanced ammonia decomposition - Xuehan Hu; Bin Guan; Lei Zhu; Chenyu Zhu; Zhongqi Zhuang; Sikai Zhao; Junyan Chen; Kaiyou Shu; Hongtao Dang; Junjie Gao; Luyang Zhang; Tiankui Zhu; et al. (Chemical Engineering Journal, 2025)

Achieving fast Zn dynamics in high-mass-loading cathode via 3D-printed hierarchical graphene architectures in zinc-ion batteries - Shixiang Yu; Yongbiao Mu; Huicun Gu; Yonglin Zhang; Shuai Zhao; Haowen Liang; Bowen Hu; Jinxing Sun; Xiaoteng Chen; Lin Zeng; Jiaming Bai; Jinglei Yang (Chemical Engineering Journal, 2025)

Developing the chemistry module for 27 fluorinated greenhouse gases (F-gases): Reactions, emissions, and implementation in GEOS-Chem - Yali Li; Lei Zhu; Juan Li; Yuyang Chen; Luke M. Western; Dickon Young; Jens Mühle; Ray F. Weiss; Paul B. Krummel; Chris R. Lunder; Song Liu; Xicheng Li; et al. (Atmospheric Environment, 2025)

A Novel Approach for Fast Microplastic Quantification in Sediments Using Machine Learning—Spectrometer Combinations - Piao Yao; Jiaming Zhang; Bin Zhou; Yang Chen; Ding He (Water, Air, & Soil Pollution, 2025)

Gastrodin inhibits hexokinase-2 mediated glycolysis to rescue rotenone-damaged PC12 cells - Min Chen; Jiaming Tian; Buyun Jia; Meng Wang; Anqi Han; Jiming Zhu; Shasha Tian; Xiaoming Gao; Baikun Li; Qinglin Li; Shanshan Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Snow-resilient mapping reveals three decades of surface water expansion on the Qinghai–Tibet Plateau - Shaofan Tang; Yilong Peng; Yongzhi Chen; Jiaming Liu; Pingping Zhang; Ying Zhang; Tingting He; Jianhua Li (Remote Sensing Applications: Society and Environment, 2025)

Lipid-mediated photoprotection confers strong light resilience in hyperaccumulator Sedum alfredii - Yanjiao Dai; Jin Chen; Yang Mao; Huidan Jiang; Wenwen Zhao; Jing Peng; Ruibing Li; Ying Wang; Purui Guo; Mengnan Zhang; Chao Zhang; Jiaming Li; et al. (Plant Science, 2025)

A normalized small waterbody size transition index for remote sensing drought monitoring - Xi Wang; Wen Zhang; Junjie Li; Zhe Wang; Zhen Zhang; Hui Wang; Yanjiao Song; Jiaming Chen; Yi Bao; Bingsun Chen; Qianyu Wang; Jia Chen; et al. (Journal of Hydrology, 2025)

Adaptive isoline interval optimization for precise contour segmentation and instance-level detection of Martian impact craters - Dong Chen; Fan Hu; Jiaming Na; Zhenxin Zhang; Zhen Cao; Liqiang Zhang; Zhizhong Kang; Jiju Poovvancheri; Norbert Pfeifer (Icarus, 2025)

Spontaneous development and characterization of an endothelial-like cell line from mandarin fish Siniperca chuatsi - Jiaming Chen; Zhong Mi; Wenfeng Zhang; Panpan Luo; Shaoping Weng; Jianguo He; Chuanfu Dong (Fish & Shellfish Immunology, 2025)

Predictive biomarkers for valproic acid-induced hepatotoxicity in Chinese patients with epilepsy: the role of metabolites and genetic polymorphisms - Dingsheng Wen; Zhuojia Chen; Ziyi Chen; Xue Bai; Hongliang Li; Juan Chen; Qiling Dai; Guoping Zhong; Jiaming Qin; Guanzhong Ni; Min Huang; Liemin Zhou; et al. (Food and Chemical Toxicology, 2025)

Enhancing phyto-microbial remediation of petroleum-contaminated soil using sophorolipid-modified biochar: Metagenomic and metabolomic insights - Yuhang Chen; Fumei Wang; Jiaqi Gao; Qinglong Liu; Jiaming Guo; Huan Liu (Environmental Research, 2025)

Experimental research on mechanised strip application process based on DEM of compressed granulated straw - Guibin Chen; Jiaming Yang; Fuzeng Yang; Qingjie Wang; Zhijie Liu; Zhengdao Liu (Biosystems Engineering, 2025)

Optimization of green development for methylene diphenyl diisocyanate industry based on synergistic benefit - Qun Shen; Qianqian Chen; Li Shang; Nannan Sun; Jiaming Gu; Tao Li; Hongbei Wang; Weisheng Yu; Xuehang Song; Wei Wei (Journal of Environmental Chemical Engineering, 2025)

Exploring the functional diversity of wild Saccharomyces cerevisiae strains for breadmaking applications - Chenwei Pan; Jiaming Li; Tianzhi Qu; Hui Liu; Weiming Xiao; Bo Chen; Anqi Chen; Jian Chen (Food Bioscience, 2025)

Improving storage stability of dairy emulsions via xanthan gum and carboxymethyl cellulose synergy - Qingyun Xu; Jiaming Li; Fanjun Meng; Yanfang Sun; Xuexian Du; Yingle Wu; Jianguo Yan; Jian Chen; Anqi Chen; Jianghua Li (Food Bioscience, 2025)

Br− as a potential suppressor of NDMA formation during ozonation of HDMS: Mechanisms and implications - Fan Zhou; Menglan Gao; Xiaobin Liao; Jiaming Zhu; Zhenkun Chen; Huatong Ma; Huayu Zhang; Jin Wang; Chenyang Liao; Mingzhi Huang; Zhimin Yang (Chemical Engineering Journal, 2025)

Fe/Mo synergistic confinement in controlled N-doped carbon nanotubes frameworks: Multiscale insights and octogen degradation in multisolvent systems–performance, interfacial mechanisms, and electronic optimization - Junlan Tang; Jinmao Ma; Panpan Zhou; Jihui Zhang; Xiaojun Wang; Yuqian Shi; Jiaming Xu; Xiangru Zhou; Yuling Bai; Jiade Lin; Chi Chen; Lincheng Zhou; et al. (Chemical Engineering Journal, 2025)

Pd/F-Al2O3 catalyst for N2O-NH3-SCR with ultrahigh low-temperature activity and resistance to inhibitory gases: Property research of being rich in oxygen vacancies with free electrons and reaction mechanisms - Zhongqi Zhuang; Bin Guan; Lei Zhu; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Kaiyou Shu; Hongtao Dang; Junjie Gao; Luyang Zhang; Tiankui Zhu; et al. (Chemical Engineering Journal, 2025)

Selective expansion of TCF7-expressing tumor-reactive T cell subpopulations during ovarian tumor-infiltrating T cell production ex vivo - Dingfeng Liu; Ting Zhang; Qinli Sun; Dongli Cai; Yanan Lou; Genyu Wang; Bowen Xie; Yicheng Zhu; Chong Wang; Zhouping Lu; Chenfei Liu; Yuan Li; et al. (Science China Life Sciences, 2025)

Numerical Simulation of an Icebreaker Ramming the Ice Ridge - Wenbo Dong; Jiaming Chen; Yufei Zhang; Shisong Wei; Guangwei He; Fang Li (Journal of Marine Science and Engineering, 2025)
During polar navigation, icebreakers frequently encounter ice ridges, which can significantly reduce navigation efficiency and even pose threats to structural safety. Therefore, studying the ramming of ice ridges by the icebreaker is of great importance. In this study, the ice ridge is decoupled into the consolidated layer and the keel for modeling. The consolidated layer is simplified as layered ice, and an innovative hybrid empirical–numerical method is used to determine the icebreaking loads. For the keel, a failure model is developed using the Mohr–Coulomb criterion in combination with the effective stress principle, accounting for shear failure in porous media and incorporating both cohesion and internal friction angle. The ship is restricted to surge motion only. A comparative analysis with the model test results was conducted to assess the accuracy of the method, with the predicted ice resistance showing deviation of 9.85% in the consolidated ice area and 10.48% in the keel area. Ablation studies were conducted to investigate the effects of different ice ridge shapes, varying retreat distances, and different ship drafts on the performance of ramming the ice ridge. The proposed method can quickly and accurately calculate ice ridge loads and predict their motion responses, providing a suitable tool for on-site rapid navigability assessment and for the design of icebreakers.

Hydrodynamic Optimization and Motion Stability Enhancement of Underwater Glider Combining CFD and MOPSO - Tian Zhang; Jiaming Wu; Xianyuan Yang; Xiaodong Chen (Journal of Marine Science and Engineering, 2025)
This study investigated the motion stability of underwater gliders and optimized their shape to enhance hydrodynamic performance. Given the critical role of stability in underwater operations, a multi-objective optimization framework was developed, focusing on the geometric configuration of hydrofoils. Computational fluid dynamics (CFD) simulations were employed, with stability assessed based on hydrodynamic moments in roll and pitch motions. A surrogate model was constructed using Kriging interpolation, leveraging Latin hypercube sampling (LHS) to generate 60 design points. Sensitivity analysis identified key shape parameters influencing stability, guiding a multi-objective particle swarm optimization (MOPSO) algorithm to explore optimal design configurations. Improvements of up to 68.91% in roll stability and 51.63% in pitch stability are achieved compared to the original model, which demonstrates the effectiveness of the proposed optimization approach. The findings provide valuable insights into the hydrodynamic design of underwater gliders, facilitating enhanced maneuverability and stability in complex marine environments.

Construction of biochar-zeolite composite for enhanced VOCs adsorption: Interfacial reinforcement and steam-driven synergistic regulation of pore formation and dealumination - Dingcheng Liang; Yajie Chang; Peipei Zhang; Yuan Liu; Chenhong Luo; Zhijun Zhang; Qiang Xie; Jiaming Liang; Kangzhou Wang; Xiao Yang; Qingping Chen; Zhucan Xie; et al. (Journal of Cleaner Production, 2025)

Dynamic interplay between core functional microbial succession and flavor metabolite formation in naturally fermented sufu: A multi-omics perspective - Chen Chen; Jiaming Li; Zahoor Ahmed; Changyue Deng; Feng Wang; Jingwei Hu; Yibin Zhou (Food Bioscience, 2025)

Efficient separation and recycling of waste wind turbine blades through in-situ generation of peroxyacetic acid - Xinyi Xu; Jiaming Liu; Jiachun Feng; Bin Chen; Shiwen Gong; Xueer Ouyang; Changxu Qin; Gang Luo; Shicheng Zhang (Resources, Conservation and Recycling, 2025)

Water quality prediction at large-Scale: Systematic assessment of decomposition-deep learning models - Jiahui Shi; Lixiao Ni; Jiaming Liu; Hui Chen; Yushen Ma; Yi Zhang; Qingwei Lin; Zhen Zhang; Hang Xu; Yiping Li (Journal of Cleaner Production, 2025)

Scale drop disease virus (SDDV) triggers ferroptosis both in mandarin fish (Siniperca chuatsi) and MFF-1 cells to facilitate virus infection via linking to transferrin receptor 1 (TfR1) - Jiaming Chen; Yuting Fu; Shuyi Chen; Shaoping Weng; Jianguo He; Chuanfu Dong (Fish & Shellfish Immunology, 2025)

Characterization of freshly-emitted particles from poplar wood burning: OC/EC, morphology, and elemental analysis under varying ignition temperatures - Junjie Cai; Jiaming Wu; Yingjun Chen (Atmospheric Environment, 2025)

Decolorization and COD Removal of Direct Sunlight-resistant Black G Dye Wastewater Using Fe/Al-C Micro-electrolysis - Pengyu Liu; Binguo Yang; Jiaming Yan; Xiaojie Chen (Water, Air, & Soil Pollution, 2025)

FeS/rGO modified cathode for enhanced electrochemical activity and TCE degradation in PS-MFC system - Chunji Li; Guanlin Chen; Jiaming Guo; Yinghao Shi; Jikun Li; Jingchun Tang (Journal of Environmental Chemical Engineering, 2025)

GACraterNet: A collaborative geometry-attribute domain network for enhanced detection of Martian impact craters - Fan Hu; Dong Chen; Jiaming Na; Zhen Cao; Zhenxin Zhang; Liqiang Zhang; Zhizhong Kang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Enhancing cancer-killing activity of PMN transfusion therapy via apoptotic modulation function of selenium nanoparticles - Chenyu Lin; Jing Wang; Yuqian Zhu; Dachuan Zhang; Xixi Huang; Jiaming Wang; Jianlin Ren; Ming Hou; Mufan Wu; Bing Shen; Bingdi Chen (Chemical Engineering Journal, 2025)

The comparison of anticrystallization effects of cellulose derivatives with polyvinylpyrrolidone and poloxamer on andrographolide: In vitro and in vivo characterization - Xiaoyi Zhang; Peixia Luo; Jiaming Wang; Lei Yang; Zipei Pang; Shufeng Chen; Yi Zhou; Linghao Qin (Carbohydrate Polymers, 2025)

Study on the division method of the excavation disturbed zone in tunnels based on continuous-discontinuous theory - Jixu Zhang; Xiaodong Fu; Chao Tan; Yongqiang Zhou; Qian Sheng; Chen Xu; Jiaming Wu (Bulletin of Engineering Geology and the Environment, 2025)

Recognition and classification techniques of marine mammal calls based on LSTM and expanded causal convolution - Wanlu Cheng; Hao Chen; Jiaming Jiang; Shuang Li; Jingjing Wang; Yanping Zhou (Frontiers in Marine Science, 2025)
Marine mammal calls play a vital role in navigation, localization, and communication. Effectively classifying these calls is essential for ecological monitoring, species conservation, and military biomimetic applications. However, traditional machine learning methods struggle to capture complex acoustic patterns, while most existing deep learning approaches rely solely on frequency-domain features and require large datasets, which limits their performance on small-scale marine mammal datasets. To address these challenges, we propose a hybrid architecture combining a time-attention Long Short-Term Memory (LSTM) network and a multi-scale dilated causal convolutional network. The model comprises three modules: (1) a frequency-domain feature extraction module employing dilated causal convolutions at multiple scales to capture multi-resolution spectral information from Mel spectrograms; (2) a time-domain feature extraction module that inputs Mel-frequency cepstral coefficients (MFCCs) into an LSTM enhanced with a time-attention mechanism to highlight key temporal features; and (3) a classification module leveraging transfer learning, where a pre-trained neural network is fine-tuned on real marine mammal call data to improve performance. Extensive experiments were conducted on vocalizations from four marine mammal species. Our proposed method outperformed existing baseline models across four evaluation metrics: accuracy, precision, recall, and F1 score, with improvements of 3%, 7%, 2%, and 4%, respectively. The results confirm the effectiveness of combining frequency- and time-domain features along with attention mechanisms and transfer learning. This hybrid approach enhances the accuracy and robustness of marine mammal call classification, especially under limited data conditions.

Anthracnose caused by Colletotrichum siamense on rambutan in China - Gengxin Chen; Jinhua Sun; Jiaming Cui; Yu Wang; Yajun Ran; Deqiang Gong; Yi Yang; Meijiao Hu; Min Li (Crop Protection, 2025)

Enhancing the separation of iron and manganese from high-iron rhodochrosite through medium-low temperature calcination and leaching - Jiaming Chen; Jiancheng Shu; Huimin Yang; Sha Zhang; Jun Luo; Jing Wang; Hongyuan Zhao; Zongchen Wei; Yong Yang; Zongyu Deng; Mengjun Chen (Process Safety and Environmental Protection, 2025)

Oxidation mechanisms of ammonia and ethanol mixed fuel by using the ReaxFF-MD simulation - Chongchong She; Chunchen Xu; Jiaming Gao; Zhi Wang; Shaohua Jin; Lijie Li; Junfeng Wang; Liang Song; Pengwan Chen; Kun Chen (Fuel, 2025)

The promotion mechanism of ammonia-based CO2 capture by hydroxyl and amine additives: A molecular dynamics and DFT study - Jiaxing Du; Wu Yang; Linlin Xu; Jiaming Chen; Zijian Song; Ben Wang; Lushi Sun (Fuel, 2025)

Associations of wildfire-derived particulate matter with hospitalization, emergency department visits and mortality: A systematic review and meta-analysis - Yiyi Wang; Jie Chen; Yujia Huang; Jiaming Wang; Yi Xiong; Tao Xue; Xu Yue; Fuping Qian; Meng Wang (Environmental Research, 2025)

ADAM17 promotes colorectal cancer migration and invasion by regulating the TGF-β/Smad signaling pathway - Jiaming Li; Tingjin Zheng; Yingzhi Xu; Mengcha Tian; Liangpan Shi; Jintu Chen; Tian Li; Zhishan Zhang (Tissue and Cell, 2025)

Measuring Off-nadir river water levels and slopes from altimeter Fully-Focused SAR mode - Jiaming Chen; Luciana Fenoglio; Jürgen Kusche (Journal of Hydrology, 2025)

Coordinated transcriptional regulation of carbohydrate-related pathways contributes to the difference of starch accumulation between starchy cassava and sugary cassava - Zehong Ding; Lili Fu; Ganlu Chen; Yan Yan; Weiwei Tie; Xianwei Meng; Jinghao Yang; Xianjin Qiu; Jiaming Zhang; Wei Hu (Carbohydrate Polymers, 2025)

Genome-wide identification of the SmPHR gene family in Salvia miltiorrhiza and SmPHR7-mediated response to phosphate starvation in Arabidopsis thaliana - Xinxin Wang; Renjun Qu; Shiwei Wang; Jiaming Peng; Juan Guo; Guanghong Cui; Tong Chen; Meilan Chen; Ye Shen (Plant Cell Reports, 2025)

Correction: Human Bone Marrow Mesenchymal Stem Cell–Derived Exosomes Attenuate Blood–Spinal Cord Barrier Disruption via the TIMP2/MMP Pathway After Acute Spinal Cord Injury - Wang Xin; Shi Qiang; Ding Jianing; Liang Jiaming; Lin Fangqi; Cai Bin; Chen Yuanyuan; Zhang Guowang; Xu Jianguang; Lian Xiaofeng (Molecular Neurobiology, 2025)

An artificial intelligence and blockchain technology-based data management framework for multicenter randomized controlled trials - Dongyuan Yun; Xiaohang Wu; Xi Chen; Yahan Yang; Yuanjun Shang; Shaopeng Liu; Dinesh Visva Gunasekeran; Duoru Lin; Lixue Liu; Lanqin Zhao; Wenben Chen; Jingjing Chen; et al. (Science Bulletin, 2025)

pLM33 provides tolerance of persistent Listeria monocytogenes ST5 to various stress conditions and also enhances its virulence - Xin Liu; Tianqi Shi; Jiaming Li; Huanyu Wu; Qing Zhao; Zhixin Fang; Yingying Liang; Quan Xiao; Min Chen; Qingli Dong; Hongzhi Zhang (Food Microbiology, 2025)

Rheological and thermal property of KH570-modified nano-SiO2 grafted xanthan gum and its application in drilling fluid system - Jingqi Shi; Long Chen; Ruihan Xie; Jiayin Zhang; Shuangcheng Pi; Jiaming Yang; Yunhai Zhao; Feng Xiong; Yongkui Zhang; Tonghui Xie (Carbohydrate Polymers, 2025)

VCU-Net: a vascular convolutional network with feature splicing for cerebrovascular image segmentation - Mengxin Li; Fan Lv; Jiaming Chen; Kunyan Zheng; Jingwen Zhao (Medical & Biological Engineering & Computing, 2025)

Selective complex leaching of Cu, Zn, and Cd from recycled copper smelting fly ash using NH3-NH4Cl system and kinetic analysis - Fan Lin; Tianya Lei; Jiancheng Shu; Mengjun Chen; Jibamu Duo; Xiangfei Zeng; Yunhui Han; Shaoqin Chen; Jiaming Chen; Weiping Huang; Jun Luo (Process Safety and Environmental Protection, 2025)

Enhanced removal of Cr(VI) from aqueous solutions by an electric field and iron–manganese oxalate composites - Shushu Liao; Kaiyuan Liang; Jiancheng Shu; Yunhui Han; Jiaming Chen; Shaoqin Chen; Jun Luo; Shengjie Wang; Mengjun Chen; Hanke Wei; Zongyu Deng (Journal of Environmental Chemical Engineering, 2025)

Development of dual polymerase spiral reaction for detection of Listeria monocytogenes and Staphylococcus aureus simultaneously - Moran Zhang; Hongzhou Chen; Jiaming Huang; Yongjin Dai; Yujuan Liu; Xiyao Zhou; Xiangfei Li; Xinyi Pang; Jing Sun; Yingjian Lu (International Journal of Food Microbiology, 2025)

Overcoming carbon deposition in non-thermal plasma catalyzed biomass tar reforming: Innovative strategies employed by GPPC systems - Heng Chen; Junguang Meng; Jiaming Tang; Xinye Wang; Yiqiang Liu; Changsheng Bu; Jubing Zhang; Changqi Liu; Hao Xie; Guilin Piao (Fuel, 2025)

Fabrication and saltiness enhancement of salt hollow particles by interface migration - Kailin Ye; Jiafeng Chen; Xinyu Zhang; Jiaming Qi; Zihan Qin; Jinmei Wang (Food Research International, 2025)

Tracking Cr(VI) removal with spectral induced polarization under ZVI and AC synergetic remediation - Xinmin Ma; Jiaming Zhang; Chen Chao; Shiliang Liu; Khalil Ur Rahman; Shupeng Li; Lili Guo; Deqiang Mao (Environmental Research, 2025)

Anti-PD-L1 blockade facilitates antitumor effects of radiofrequency ablation by improving tumor immune microenvironment in hepatocellular carcinoma - Jiahua Liang; Mingjian Ma; Wei Feng; Qiongcong Xu; Dong Chen; Jiaming Lai; Jiancong Chen (Apoptosis, 2025)

Fish Community Diversity and Spatiotemporal Dynamics in the Downstream of the Fujiang River Based on Environmental DNA - Jiaming Zhang; Yifang Chen; Xinxin Zhou; Jiaxin Huang; Xiaohan Dong; Shuli Zhu; Yanjun Shen (Fishes, 2025)
Hydrological changes caused by dam construction are among the primary drivers of global freshwater biodiversity decline. To assess the current status of fish community diversity and examine the impacts of cascade hydropower development on fish diversity, this study employed environmental DNA (eDNA) technology from 2023 to 2024 to conduct seasonal surveys at 18 sampling sites across six river segments separated by five dams in the downstream section of the Fujiang River. The study aimed to uncover the temporal and spatial dynamics of fish diversity and community structure, as well as to analyze the influence of environmental factors on these patterns. The results identified 84 fish species spanning 60 genera, 19 families, and 7 orders, including 2 nationally protected species, 11 endemic species of the upper Yangtze River, and 13 alien species. The cascade dams were found to have significantly reduced fish diversity compared to historical records, with a marked decline in native species and a rise in alien species, contributing to the miniaturization and homogenization of fish communities. Environmental factor analysis revealed that chemical oxygen demand (COD), dissolved oxygen (DO), total dissolved solids (TDS), electrical conductivity (EC), and reservoir formation time were significant drivers of fish community structure and diversity. This study provides essential baseline data on fish diversity under the influence of cascade hydropower development in the Fujiang River. It also offers valuable insights into the current status of fish resources and supports efforts in fish conservation and aquatic ecosystem management in the region.

First report of Colletotrichum siamense and C. tropicale causing anthracnose of Syngonium podophyllum in China - Jiaming Cui; Jinhua Sun; Min Li; Gengxin Chen; Jinyu Yang; Yu Wang; Tianyu Huang; Deqiang Gong; Meijiao Hu (Crop Protection, 2025)

Adaptive fuzzy optimal output-feedback fault-tolerant control for the USV system with intermittent actuator faults - Jiaming Zhang; Wenjun Zhang; C.L. Philip Chen; Shaocheng Tong (Ocean Engineering, 2025)

Excessive nitrogen application reduces eating quality by changing the starch molecular structure and physicochemical properties of inferior grains - Can Zhao; Yue Chen; Kunlun Liu; Guangming Liu; Jiaming Lu; Weiling Wang; Zhongyang Huo (Journal of Cereal Science, 2025)

Enhanced steam reforming of benzene in a two-stage catalytic system: Insights into metal synergies and carbon deposition evolution - Heng Chen; Junguang Meng; Jiaming Tang; Xinye Wang; Changsheng Bu; Jubing Zhang; Changqi Liu; Hao Xie; Yuan Sun (Fuel, 2025)

Insights into the combustion mechanisms of turpentine oil based on ReaxFF molecular dynamics simulations - Chongchong She; Tiancheng Zhang; Jiaming Gao; Zhi Wang; Shaohua Jin; Lijie Li; Junfeng Wang; Liang Song; Pengwan Chen; Kun Chen (Fuel, 2025)

Effect of heat treatment on the stability of ultrasound-assisted cross-linked myofibrillar protein-stabilized emulsion filler phases via rheology and tribology - Ye Tao; Jiaming Cai; Peng Wang; Jiahui Chen; Lei Zhou; Qi Wang; Zhen Li; Jingyu Wang; Xinglian Xu (Food Hydrocolloids, 2025)

The impact of short-term exposure to criteria air pollutants on sleep disturbance among young adults: A nationwide analysis in 261 Chinese cities - Chunliang Wang; Kai Su; Linming Hu; Xinjie Dai; Xixian Fang; Chunhui Yang; Ruitong Zhang; Jiaming Liu; Junteng Zhou; Chenyu Xu; Hualu Gan; Lingyan Chen; et al. (Environmental Research, 2025)

Acoustic micromixing in a serpentine channel with sharp teeth for controllable nanomaterial synthesis - Bin Ran; Bo Liu; Chaozhan Chen; Wenqiang Tong; Jiaming Shi; Jiaxi Du; Zhihang Yu; Siwei Bai; Huaying Chen; Yonggang Zhu (Chemical Engineering Journal, 2025)

Calibration of the Solar X-ray Detector on-board the Macao Science Satellite-1B for Soft X-ray Detection - Man-Hei Ng; Xiaoping Zhang; Jianwu Chen; Yongqiang Shi; Fuchang Zuo; Wenxi Peng; Weichun Fu; Liansheng Li; Pengwei Luo; Chi-Long Tang; Guozheng Zhang; Zhiwu Mei; et al. (Science China Earth Sciences, 2025)

Integrating UAV, UGV and UAV-UGV collaboration in future industrialized agriculture: Analysis, opportunities and challenges - Zhigang Ren; Han Zheng; Jian Chen; Tao Chen; Pengyang Xie; Yunzhe Xu; Jiaming Deng; Huanzhe Wang; Mingjiang Sun; Wenchi Jiao (Computers and Electronics in Agriculture, 2024)

The impact of Neoporphyra haitanensis dietary supplement on astaxanthin esters and fatty acids accumulation associated with immune promotion in Pacific white shrimp (Litopenaeus vannamei) - Qian Shen; Shuang Li; Shuyu Zhang; Jiaming Xu; Haimin Chen; Qijun Luo; Rui Yang; Juanjuan Chen (Aquaculture, 2024)

Constitutive modelling of the shakedown response of sensitive clay to undrained long-term cyclic loads incorporating structural destruction - Jiaming Liu; Chuang Zhao; Hongming Liu; Xuecheng Bian; Yunmin Chen (Computers and Geotechnics, 2024)

Electroactive supramolecular nanoprobes for electrochemical detection of rituximab in non-Hodgkon’s lymphoma patients - Zhiwei Chen; Zheng Zhao; Jiaming Yuan; Qiaoxuan Zhang; Yufeng Wu; Qingjin Wu; Yuheng Liao; Jia-Huan Qu; Ning Gan; Zhengjin Jiang; Qiqin Wang (Chemical Engineering Journal, 2024)

Influence of staggered guide vane on hydraulic performance of reactor coolant pump - Binhao Liu; Daoxing Ye; Junlin Chen; Mengke Wu; Rui Deng; Junyu Zhang; Jiaming Han (Annals of Nuclear Energy, 2024)

Corrigendum to “Implanted 3D gelatin microcryogel enables low-dose cell therapy for osteoarthritis by preserving the viability and function of umbilical cord MSCs” [Chem. Eng. J. 416 (2021) 129140] - Xiaoguang Zhang; Shaokai Liu; Zhenxing Wang; Chao Luo; Zhipeng Dai; Jiaming Sun; Yong Liu; Zengwu Shao; Shuhua Yang; Hui Wang; Juan Wang; Wei Chen; et al. (Chemical Engineering Journal, 2024)

Sensitive and quick electrochemiluminescence biosensor for the detection of reactive oxygen species in seminal plasma based on the valence regulation of gold nanoclusters - Lingjun Cheng; Yuanyuan Yang; Shaobin Lin; Canping Su; Mingming You; Yating Liu; Qingfei He; Jiaming Chen; Zhenyu Lin; Guolin Hong (Analytica Chimica Acta, 2024)

Carbonate system in the subtropical Jiulong River Estuary and CO2 flux estimation under modulation of tidal cycle - Weicong Chen; Heng Sun; Zhongyong Gao; Jiaming Lin; Min Xu; Aijun Wang; Shuqin Tao (Acta Oceanologica Sinica, 2024)

ILP1 and NTR1 affect the stability of U6 snRNA during spliceosome complex disassembly in Arabidopsis - Jiaming Wu; Wei Chen; Shengchao Ge; Xueliang Liu; Junling Shan; Meishan Zhang; Yuan Su; Yunfeng Liu (Plant Science, 2024)

Optimal classification of radiant time series for cooling load calculation of building air-conditioning systems - Jing Ren; Youming Chen; Xinchao Zhang; Jiaming Liu (Energy and Buildings, 2024)

Significantly enhancing high-temperature piezoelectric response and Tdr of BF-BT-based ceramics through multi-component optimization strategy - Huabin Yang; Jiaming Zhu; Xueting Wang; Qiuling Luo; Hua Tan; Haibo Zhang; Jiwen Xu; Qiaohong Chen (Chemical Engineering Journal, 2024)

A hybrid PM2.5 interval concentration prediction framework based on multi-factor interval decomposition reconstruction strategy and attention mechanism - Jiaming Zhu; Lili Niu; Peng Zheng; Huayou Chen; Jinpei Liu (Atmospheric Environment, 2024)

The New Roles of traf6 Gene Involved in the Development of Zebrafish Liver and Gonads - Hongyan Xu; Wenzhuo Ban; Jiaming Tian; Jianfei Xu; Zhimin Tan; Sendong Li; Kaili Chen; Mi Ou; Kaibin Li (Marine Biotechnology, 2024)

The resistance to anoikis, mediated by Spp1, and the evasion of immune surveillance facilitate the invasion and metastasis of hepatocellular carcinoma - Zhengwei Zhang; Xiaoning Chen; Yapeng Li; Feng Zhang; Zhen Quan; Zhuo Wang; Yang Yang; Wei Si; Yuting Xiong; Jiaming Ju; Yu Bian; Shibo Sun (Apoptosis, 2024)
Anoikis-Related Genes (ARGs) lead to the organism manifesting resistance to anoikis and are associated with unfavorable prognostic outcomes across various malignancies.Therefore, it is crucial to identify the pivotal target genes related to anoikis in HCC .We found that ARGs were significantly correlated with prognosis and immune responses in HCC. The core gene, SPP1, notably promoted anoikis resistance and metastasis in HCC through both in vivo and in vitro studies. The PI3K-Akt-mTOR pathway played a critical role in anoikis suppression within HCC contexts. Our research unveiled SPP1’s role in enhancing PKCα phosphorylation, which in turn activated the PI3K-Akt-mTOR cascade. Additionally, SPP1 was identified as a key regulator of MDSCs and Tregs migration, directly affecting their immunosuppressive capabilities.These findings indicate that in HCC, SPP1 promoted anoikis resistance and facilitated immune evasion by modulating MDSCs and Tregs. Graphical Abstract

Application of rheology and interfacial rheology to investigate the emulsion stability of ultrasound-assisted cross-linked myofibrillar protein: Effects of oil phase types - Ye Tao; Jiaming Cai; Peng Wang; Jiahui Chen; Lei Zhou; Weiyi Zhang; Xinglian Xu (Food Hydrocolloids, 2024)

LSGNet: A lightweight convolutional neural network model for tomato disease identification - Shengxian Yang; Licai Zhang; Jianwu Lin; Tomislav Cernava; Jitong Cai; Renyong Pan; Jiaming Liu; Xingtian Wen; Xiaoyulong Chen; Xin Zhang (Crop Protection, 2024)

Effects of DeSUMOylated Spastin on AMPA Receptor Surface Delivery and Synaptic Function Are Enhanced by Phosphorylating at Ser210 - Wenbin Zhang; Jiaqi Zhang; Zhongqi Zhang; Shuhan Cha; Jiong Li; Li Chen; Jiaming Wu; Jijun Teng; Guoqing Guo; Jifeng Zhang (Molecular Neurobiology, 2024)

Genome-wide identification and expression analysis of the SOD gene family under biotic and abiotic stresses in sweet orange - Xulin Li; Ke Wen; Tuo Yin; Chaoying Chen; Ling Zhu; Xiuyao Yang; Yinqiang Zi; Ke Zhao; Jiaming Zhang; Hanyao Zhang (Plant Biotechnology Reports, 2024)

Memristive switching in the surface of a charge–density–wave topological semimetal - Jianwen Ma; Xianghao Meng; Binhua Zhang; Yuxiang Wang; Yicheng Mou; Wenting Lin; Yannan Dai; Luqiu Chen; Haonan Wang; Haoqi Wu; Jiaming Gu; Jiayu Wang; et al. (Science Bulletin, 2024)

First report of Colletotrichum siamense causing leaf spot on silver date palm in China - Jinyu Yang; Min Li; Gengxin Chen; Jinhua Sun; Wu Zhang; Jiaming Cui; Yu Wang; Deqiang Gong; Meijiao Hu (Crop Protection, 2024)

A study on ice resistance prediction based on deep learning data generation method - Qianyang Sun; Jiaming Chen; Li Zhou; Shifeng Ding; Sen Han (Ocean Engineering, 2024)

Orbital forcing of aridity/humidity fluctuations in the Hexi Corridor and Alxa Plateau, NW China, during the last 1.8 million years - Dianbao Chen; Jiaming Yang; Junsheng Nie; Fei Wang; Qinhong Mo; Baotian Pan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

eDNA reveals spatial homogenization of fish diversity in a mountain river affected by a reservoir cascade - Ruli Cheng; Xinxin Zhou; Yufeng Zhang; Qinghua Li; Jiaming Zhang; Yang Luo; Qiliang Chen; Zhihao Liu; Yingwen Li; Yanjun Shen (Journal of Environmental Management, 2024)

Cryopreserved leukapheresis material can be transferred from controlled rate freezers to ultracold storage at warmer temperatures without affecting downstream CAR-T cell culture performance and in-vitro functionality - Jiaming Wei; Katherine Chaney; Woo Jin Shim; Heyu Chen; Grace Leonard; Sean O'Brien; Ziyan Liu; Jinlin Jiang; Robert Ulrey (Cryobiology, 2024)

Alterations in Dynamic Functional Connectivity in Patients with Cerebral Small Vessel Disease - Futao Chen; Qian Chen; Yajing Zhu; Cong Long; Jiaming Lu; Yaoxian Jiang; Xin Zhang; Bing Zhang (Translational Stroke Research, 2024)
Cerebral small vessel disease (CSVD) is a common disease that seriously endangers people’s health, and is easily overlooked by both patients and clinicians due to its near-silent onset. Dynamic functional connectivity (DFC) is a new concept focusing on the dynamic features and patterns of brain networks that represents a powerful tool for gaining novel insight into neurological diseases. To assess alterations in DFC in CSVD patients, and the correlation of DFC with cognitive function. We enrolled 35 CSVD patients and 31 normal control subjects (NC). Resting-state functional MRI (rs-fMRI) with a sliding-window approach and k -means clustering based on independent component analysis (ICA) was used to evaluate DFC. The temporal properties of fractional windows and the mean dwell time in each state, as well as the number of transitions between each pair of DFC states, were calculated. Additionally, we assessed the functional connectivity (FC) strength of the dynamic states and the associations of altered neuroimaging measures with cognitive performance. A dynamic analysis of all included subjects suggested four distinct functional connectivity states. Compared with the NC group, the CSVD group had more fractional windows and longer mean dwell times in state 4 characterized by sparse FC both inter-network and intra-networks. Additionally, the CSVD group had a reduced number of windows and shorter mean dwell times compared to the NC group in state 3 characterized by highly positive FC between the somatomotor and visual networks, and negative FC in the basal ganglia and somatomotor and visual networks. The number of transitions between state 2 and state 3 and between state 3 and state 4 was significantly reduced in the CSVD group compared to the NC group. Moreover, there was a significant difference in the FC strength between the two groups, and the altered temporal properties of DFC were significantly related to cognitive performance. Our study indicated that CSVD is characterized by altered temporal properties in DFC that may be sensitive neuroimaging biomarkers for early disease identification. Further study of DFC alterations could help us to better understand the progressive dysfunction of networks in CSVD patients.

Rab18 maintains homeostasis of subcutaneous adipose tissue to prevent obesity-induced metabolic disorders - Jiaming Liu; Liangkui Li; Dijin Xu; Yuqi Li; Tao Chen; Yeyang Liu; Yuqian Bao; Yan Wang; Longyan Yang; Peng Li; Li Xu (Science China Life Sciences, 2024)

Effect of temperature on the occurrence of Metschnikowia bicuspidata disease in Eriocheir sinensis - Hongbo Jiang; Gangnan Cao; Jie Bao; Chengcheng Feng; Xiaodong Li; Yuanyuan Tan; Jiaming Dong; Qijun Chen (Aquaculture, 2024)

An injectable antibacterial hydrogel with bacterial-targeting properties for subcutaneous suppuration treatment - Yongchang Tian; Rong Zhang; Jiaming Cui; Yaowei Zhu; Minghui Sun; Ian W. Hamley; Chunsheng Xiao; Li Chen (Chemical Engineering Journal, 2024)

Establishment of a gill cell line from yellowfin seabream ( Acanthopagrus latus ) for studying Amyloodinium ocellatum infection of fish - Zhicheng Li; Jingyu Zhuang; Jiaming Chen; Jizhen Cao; Qing Han; Zhi Luo; Baotun Wang; Hebing Wang; Anxing Li (Journal of Fish Diseases, 2024)
Amyloodinium ocellatum is among the most devastating protozoan parasites, causing huge economic losses in the mariculture industry. However, the pathogenesis of amyloodiniosis remains unknown, hindering the development of targeted anti‐parasitic drugs. The A. ocellatum in vitro model is an indispensable tool for investigating the pathogenic mechanism of amyloodiniosis at the cellular and molecular levels. The present work developed a new cell line, ALG, from the gill of yellowfin seabream ( Acanthopagrus latus ). The cell line was routinely cultured at 28°C in Dulbecco's modified Eagle medium (DMEM) supplemented with 15% fetal bovine serum (FBS). ALG cells were adherent and exhibited an epithelioid morphology; the cells were stably passed over 30 generations and successfully cryopreserved. The cell line derived from A. latus was identified based on partial sequence amplification and sequencing of cytochrome B ( Cyt b ). The ALG was seeded onto transwell inserts and found to be a platform for in vitro infection of A. ocellatum , with a 37.23 ± 5.75% infection rate. Furthermore, scanning electron microscopy (SEM) revealed that A. ocellatum parasitizes cell monolayers via rhizoids. A. ocellatum infection increased the expression of apoptosis and inflammation‐related genes, including caspase 3 ( Casp 3 ), interleukin 1 ( IL‐1 ), interleukin 10 ( IL‐10 ), tumour necrosis factor‐alpha ( TNF‐α ), in vivo or in vitro. These results demonstrated that the in vitro gill cell monolayer successfully recapitulated in vivo A. latus host responses to A. ocellatum infection. The ALG cell line holds great promise as a valuable tool for investigating parasite–host interactions in vitro.

Fabrication of hyaluronic acid-altered gold complex delivery for head and neck squamous cell carcinoma therapy with high antitumor efficacy and low in vivo toxicity - Shizhi He; Jiaming Chen; Yanming Zhao; Ru Wang; Yurong He; Shaoshi Chen; Yifan Yang; Changyu Zhu; Jingyang Zhao; Jugao Fang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Development of a 3D point cloud reconstruction-based apple canopy liquid sedimentation model - Chongchong Chen; Yalan Jia; Jiaming Zhang; Linsen Yang; Yaxiong Wang; Feng Kang (Journal of Cleaner Production, 2024)

A novel method for efficiently recycling platinum group metals and copper by Co-smelting spent automobile catalysts with waste-printed circuit boards - Rong Huang; Songshan Zhou; Jiaming Chen; Xiangfei Zeng; Yunhui Han; Jinchuan Qin; Yao Huang; Fan Lin; Xi Yu; Shushu Liao; Zhiqiang Chen; Yubin Han; et al. (Journal of Cleaner Production, 2024)

Molecular Determinants of Neurocognitive Deficits in Glioma: Based on 2021 WHO Classification - Kun Zhang; Tianrui Yang; Yu Xia; Xiaopeng Guo; Wenlin Chen; Lijun Wang; Junlin Li; Jiaming Wu; Zhiyuan Xiao; Xin Zhang; Wenwen Jiang; Dongrui Xu; et al. (Journal of Molecular Neuroscience, 2024)
Cognitive impairment is a common feature among patients with diffuse glioma. The objective of the study is to investigate the relationship between preoperative cognitive function and clinical as well as molecular factors, firstly based on the new 2021 World Health Organization’s updated classification of central nervous system tumors. A total of 110 diffuse glioma patients enrolled underwent preoperative cognitive assessments using the Mini-Mental State Examination and Montreal Cognitive Assessment. Clinical information was collected from medical records, and gene sequencing was performed to analyze the 18 most influenced genes. The differences in cognitive function between patients with and without glioblastoma were compared under both the 2016 and 2021 WHO classification of tumors of the central nervous system to assess their effect of differentiation on cognition. The study found that age, tumor location, and glioblastoma had significant differences in cognitive function. Several genetic alterations were significantly correlated with cognition. Especially, IDH , CIC , and ATRX are positively correlated with several cognitive domains, while most other genes are negatively correlated. For most focused genes, patients with a low number of genetic alterations tended to have better cognitive function. Our study suggested that, in addition to clinical characteristics such as age, histological type, and tumor location, molecular characteristics play a crucial role in cognitive function. Further research into the mechanisms by which tumors affect brain function is expected to enhance the quality of life for glioma patients. This study highlights the importance of considering both clinical and molecular factors in the management of glioma patients to improve cognitive outcomes.

Tailored amphiphilic polymers enable stabilized biologics in hyperthermal water and freeze-drying process - Xiaowen Liu; Jian Chen; Jiaming Zhong; Fener Chen (Chemical Engineering Journal, 2024)

Activation of persulfate by biochar-supported sulfidized nanoscale zero-valent iron for degradation of ciprofloxacin in aqueous solution: process optimization and degradation pathway - Wenjing Xue; Xinyu Chen; Hongdou Liu; Jun Li; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Yang Gao; Rongzhong Wang; Yiqun Xu (Environmental Science and Pollution Research, 2024)

Effectively solve the obstacle in the old residential building energy-saving renovation from the perspective of a four-party evolutionary game - Peng Wang; Haiyun Chen; Zhiyuan Si; Ling Jia; Jiaming Wang; Keying Li; Chenglong Wang (Environmental Science and Pollution Research, 2024)

High-efficient photocatalytic degradation of multiple pollutants by CdPS3 nanosheets - Bingda Li; Jiaming Song; Yuting Li; Chaoying Meng; Shuxian Wang; Linghao Zong; Honggang Ye; Yishuai Jing; Feng Teng; Peng Hu; Haibo Fan; Guangde Chen; et al. (Process Safety and Environmental Protection, 2024)

Exploring the relationship between the interfacial properties and emulsion properties of ultrasound-assisted cross-linked myofibrillar protein - Ye Tao; Jiaming Cai; Peng Wang; Jiahui Chen; Lei Zhou; Zongyun Yang; Xinglian Xu (Food Hydrocolloids, 2024)

Enhanced immobilization of cadmium in contaminated paddy soil by biochar-supported sulfidized nanoscale zero-valent iron - Yiqun Xu; Shan Cao; Xinyu Chen; Jun Li; Hongdou Liu; Yang Gao; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Wenjing Xue (Journal of Soils and Sediments, 2024)

Using geodetic measurements derived terrestrial water storage to investigate the characteristics of drought in Yunnan, China - Chao Chen; Rong Zou; Zhiwei Fang; Jiaming Cao; Qi Wang (GPS Solutions, 2024)
The use of the global navigation satellite system (GNSS) for monitoring changes in terrestrial water storage (TWS) is growing. However, the density of GNSS stations is sparse in most areas, and the widely used Green’s function (GF) method cannot provide a satisfactory resolution for inversion problems. As the Slepian basis function (SBF) method has been successfully used for gravity inversions, GNSS geodesists have recently applied the SBF method to GNSS displacements. However, the evaluation of TWS differences inferred from GNSS using the SBF and the GF has been rarely assessed. In this study, we use both the GF and the SBF methods to investigate the TWS in Yunnan by using more than ten years (2010–2021) of GNSS observations. We observe a remarkable consistency between the two inversion methods employed for GNSS data, as well as a strong agreement with equivalent water heights (EWH) inferred from the Gravity Recovery and Climate Experiment (GRACE) and GRACE Follow-On (GFO), hydrological model (GLDAS-NOAH), and precipitation data, despite variations in the amplitude. Furthermore, affected by monsoon climate and topography, Yunnan is prone to drought. We analyze the main nine drought events, evaluate the connection between GNSS-inverted TWS during 2010–2021, and find that almost all droughts in Yunnan occurred during the "trough period" within the GNSS-DSI.

Ingestion and biodegradation of disposable surgical masks by yellow mealworms Tenebrio molitor larvae: Differences in mask layers and effects on the larval gut microbiome - Jiaming Wang; Chi Zhang; Xin Zhao; Yue Weng; Xinrui Nan; Xiaoyu Han; Chen Li; Baoqin Liu (Science of The Total Environment, 2023)

Recent advances in nanomaterial-enhanced persulfate activation for organic pollutants removal: Electron transfer, surface reactions, and radical generation - Dingren Ma; Ji Mei; Qiwen Liang; Yimu Jiao; Tianyu Hu; Jingchen Chen; Jiaming Wang; Hao Zhou; Qiyu Lian; Mingzhe Sun; Dehua Xia; Tianqi Wang (Journal of Environmental Chemical Engineering, 2023)

Coffee grounds-derived carbon quantum dots as peroxidase mimetics for colorimetric and fluorometric detection of ascorbic acid - Yuyan Zhu; Xiang Deng; Jiaming Chen; Zhiyuan Hu; Fengshou Wu (Food Chemistry, 2023)

Spatiotemporal distribution of phytoplankton community structure and its relationship with environmental factors in Hongze Lake, China - Jiahui Shi; Lixiao Ni; Jiaming Liu; Chen Xu; Jianhua Zhang; Xuqing Chen (Urban Climate, 2023)

Enhanced recovery of high purity Cu powder from reclaimed copper smelting fly ash by NH3·H2O–NH4Cl slurry electrolysis system - Jiaming Chen; Tianya Lei; Jiancheng Shu; Wenxing Cao; Xiangfei Zeng; Fan Lin; Shushu Liao; Mengjun Chen; Liang Wei; Weiping Huang (Journal of Cleaner Production, 2023)

Thermal-and-mechanochemical recycling of waste polypropylene into maleated-epoxided degradation products as warm-mix asphalt modifier: Performance improvement and production mechanism analysis - Xiong Xu; Yaming Chu; Yi Luo; Yuhao Peng; Nannan Yang; Jiaming Yan; Xuyong Chen; Fuliao Zou; Anand Sreeram (Journal of Cleaner Production, 2023)

Immobilization of cadmium in river sediments by different modified nanoscale zero-valent iron: performance, mechanisms, and Fe dissolution - Wenjing Xue; Hongdou Liu; Jun Li; Xinyu Chen; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Shan Cao; Yang Gao; Rongzhong Wang; Yiqun Xu (Environmental Science and Pollution Research, 2023)

Multi-objective shape optimization of autonomous underwater vehicle by coupling CFD simulation with genetic algorithm - Xiaodong Chen; Liang Yu; Leo Yang Liu; Lele Yang; Shunyuan Xu; Jiaming Wu (Ocean Engineering, 2023)

Seismic response analysis of submerged floating tunnel considering non-uniform excitation and flexible-support boundary effect - Jiaming Xie; Jing Li; Jianyun Chen; Qiang Xu (Ocean Engineering, 2023)

Zwitterionic loose polyamide nanofiltration membrane with good antifouling properties for efficient removal of humic acid and dyes - Chengbao Geng; Fangbo Zhao; Hongyan Niu; Jiaming Zhang; Yang Liu; Lijia Liu; Hongxing Dong; Zhiguo Li; Hongxu Chen (Journal of Environmental Chemical Engineering, 2023)

Extreme low-temperature events can alleviate micronutrient deficiencies while increasing potential health risks from heavy metals in rice - Min Kang; Xue Wang; Jiankun Chen; Qizhao Fang; Jiaming Liu; Liang Tang; Leilei Liu; Weixing Cao; Yan Zhu; Bing Liu (Environmental Pollution, 2023)

Catalytic degradation of bisphenol a (BPA) in water by immobilizing silver-loaded graphene oxide (GO-Ag) in ultrafiltration membrane with finger-like structure - Ye Yang; Fangbo Zhao; Liu Yang; Jiaming Zhang; Hee-Deung Park; Zhiguo Li; Hongxu Chen; Ximeng Zhang; Mingjin Gao (Chemical Engineering Journal, 2023)

Evolutionary characterization and pathogenicity of Getah virus from pigs in Guangdong Province of China - Jinghua Pan; Haoquan Zhang; Xiuqiao Chen; Mengyi Zeng; Hui Han; Yajing Guo; Jiaming Li; Shicheng Luo; Guangzhi Yan; Shengnan Chen; Meilian Mo; Mingjie Liu; et al. (Archives of Virology, 2023)

Recent advances in sulfidized nanoscale zero-valent iron materials for environmental remediation and challenges - Wenjing Xue; Jun Li; Xinyu Chen; Hongdou Liu; Siqi Wen; Xiaoyu Shi; Jiaming Guo; Yang Gao; Jian Xu; Yiqun Xu (Environmental Science and Pollution Research, 2023)

Comparing extraction methods for analyzing n-alkyl lipids in shelf sediments from the China Sea - Jiaming Zhou; Xiaoxiao Zhao; Xin Chen; Liang Dong (Organic Geochemistry, 2023)

Visible-light photocatalytic degradation of water-soluble polyvinyl alcohol in aqueous solution by Cu2O@TiO2: Optimization of conditions, mechanisms and toxicity analysis - Jiaming Zhang; Zhenqi Zhou; Bing Xiao; Chenxu Zhou; Zhongqin Jiang; Yinna Liang; Zhuo Sun; Jianhua Xiong; Guoning Chen; Hongxiang Zhu; Shuangfei Wang (Journal of Environmental Management, 2023)

Influence of hemin on structure and emulsifying properties of soybean protein isolate - Jiaming Zhang; Yangyang Jia; Wenjin Wu; Yingying Zhang; Ping Chen; Xiaofang Li; Xuetuan Wei; Chunmei Li; Kaikai Li (Food Chemistry, 2023)

An interval-valued carbon price forecasting method based on web search data and social media sentiment - Jinpei Liu; Xue Li; Piao Wang; Huayou Chen; Jiaming Zhu (Environmental Science and Pollution Research, 2023)

Numerical investigation of flow similarity of rice grains in friction rice mill and establishment of scale-up rule - Anqi Li; Fuguo Jia; Jiaming Fei; Yanlong Han; Peiyu Chen; Wenyu Feng; Xianzhi Hao; Shaohang Shen; Hao Li (Computers and Electronics in Agriculture, 2023)

Dynamic retention of thallium(I) on humic acid: Novel insights into the heterogeneous complexation ability and responsiveness - Wanpeng Chen; Xiaoliu Huangfu; Jiaming Xiong; Hongxia Liu; Qiang He (Water Research, 2023)

Multiscale Feature Fusion for Hyperspectral Marine Oil Spill Image Segmentation - Guorong Chen; Jiaming Huang; Tingting Wen; Chongling Du; Yuting Lin; Yanbing Xiao (Journal of Marine Science and Engineering, 2023)
Oil spills have always been a threat to the marine ecological environment; thus, it is important to identify and divide oil spill areas on the ocean surface into segments after an oil spill accident occurs to protect the marine ecological environment. However, oil spill area segmentation using ordinary optical images is greatly interfered with by the absorption of light by the deep sea and the distribution of algal organisms on the ocean surface, and it is difficult to improve segmentation accuracy. To address the above problems, a hyperspectral ocean oil spill image segmentation model with multiscale feature fusion (MFFHOSS-Net) is proposed. Specifically, the oil spill segmentation dataset was created using hyperspectral image data from NASA for the Gulf of Mexico oil spill, small-size images after the waveband filtering of the hyperspectral images were generated and the oil spill images were annotated. The model makes full use of having different layers with different characteristics by fusing feature maps of different scales. In addition, an attention mechanism was used to effectively fuse these features to improve the oil spill region segmentation accuracy. A case study, ablation experiments and model evaluation were also carried out in this work. Compared with other models, our proposed method achieved good results according to various evaluation metrics.

Efficient separation and comprehensive extraction of aluminum, silicon, and iron from coal fly ash by a cascade extraction method - Xiaodan Zhao; Li Zeng; Jiaming Guo; Qiaoling Zhu; Zhuojun Huang; Lifeng Lin; Xuanang Chen; Jing Cao; Zhen Zhou (Journal of Cleaner Production, 2023)

Study on dynamic response mechanism of rice grains in friction rice mill and scale-up approach of parameter based on discrete element method - Anqi Li; Fuguo Jia; Yanlong Han; Peiyu Chen; Yinglong Wang; Jincheng Zhang; Xianzhi Hao; Jiaming Fei; Shaohang Shen; Wenyu Feng (Innovative Food Science & Emerging Technologies, 2023)

Effect of gastrodin against cognitive impairment and neurodegeneration in APP/PS1 mice via regulating gut microbiota–gut–brain axis - Yuhe Zhang; Yan Chen; Shushu Yuan; Qingxia Yu; Jianjiong Fu; Luyun Chen; Jiaming Liu; Yuping He (Experimental Brain Research, 2023)

A mandarinfish Siniperca chuatsi infection and vaccination model for SDDV and efficacy evaluation of the formalin-killed cell vaccine in yellowfin seabream Acanthopagrus latus - Yuting Fu; Yong Li; Jiaming Chen; Fangzhao Yu; Xiangrong Liu; Weixuan Fu; Hongrun Pan; Wangdong Li; Shaoping Weng; Jianguo He; Chuanfu Dong (Aquaculture, 2023)

The mechanism of bran layer removal in friction rice mills - Jiaming Fei; Wenyu Feng; Fuguo Jia; Yanlong Han; Peiyu Chen; Anqi Li; Yinglong Wang; Jincheng Zhang; Shaohang Shen; Xianzhi Hao (Biosystems Engineering, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A minimal genome design to maximally guarantee fertile inter-subspecific hybrid rice - Penghui Zhou; Zhengji Wang; Xingchen Zhu; Yao Tang; Liang Ye; Huihui Yu; Yating Li; Ningke Zhang; Ting Liu; Tian Wang; Yuying Wu; Dengyun Cao; et al. (Molecular Plant, 2023)

A conceptual model for the shakedown response of soft clay to high-cycle, low-amplitude undrained loading - Chuang Zhao; Jiaming Liu; Hongming Liu; Xuecheng Bian; Yunmin Chen (Computers and Geotechnics, 2023)

Antibacterial anodic aluminium oxide-copper coatings on aluminium alloys: preparation and long-term antibacterial performance - Jiahuan Chen; Zhen He; Jiaming Liu; Yuxin Wang; Michael Hodgson; Wei Gao (Chemical Engineering Journal, 2023)

An improved spatial case-based reasoning considering multiple spatial drivers of geographic events and its application in landslide susceptibility mapping - Zheng Zhao; Jianhua Chen; Jiaming Yao; Kaihang Xu; Yangyang Liao; Huawei Xie; Xianxia Gan (CATENA, 2023)

Selection and truncation of aptamers as fluorescence sensing platforms for selective and sensitive detection of nitrofurazone - Xu Wen; Xueling Yan; Xiaoling Zheng; Qiming Kou; Lulan Yang; Jiaming Tang; Xingyue Chen; Yong Xie; Tao Le (Analytica Chimica Acta, 2023)

Evaluation of Sentinel-3A altimetry over Songhua river Basin - Jiaming Chen; Luciana Fenoglio; Jürgen Kusche; Jingjuan Liao; Hakan Uyanik; Zulfikar Adlan Nadzir; Yanhan Lou (Journal of Hydrology, 2023)

Biological hydrogen with industrial potential: Improvement and prospection in biohydrogen production - Weixian Chen; Tianpei Li; Yangyi Ren; Jiaming Wang; Hui Chen; Qiang Wang (Journal of Cleaner Production, 2023)

Improved catalytic activity and stability of Cu/ZnO catalyst by boron oxide modification for low-temperature methanol synthesis - Fei Chen; Jiaming Liang; Fan Wang; Xiaoyu Guo; Weizhe Gao; Yasuharu Kugue; Yingluo He; Guohui Yang; Prasert Reubroycharoen; Tharapong Vitidsant; Noritatsu Tsubaki (Chemical Engineering Journal, 2023)

Self-repairing thermal energy storage gels demonstrating superior thermophysical properties and wearability towards personal thermal management in static and dynamic modes - Yingying Luo; Hongjiao Wu; Junpeng Qiao; Jiaming Zhang; Kai Liu; Liqing Zou; Ying Chen; Pengcheng Lin (Chemical Engineering Journal, 2023)

Impact of biochar colloids on thallium(I) transport in water-saturated porous media: Effects of pH and ionic strength - Yu Cao; Chengxue Ma; Jinni Yao; Wanpeng Chen; Li Gu; Hongxia Liu; Caihong Liu; Jiaming Xiong; Xiaoliu Huangfu (Chemosphere, 2023)

Breakage mechanism of brown rice grain during rubber roll hulling - Peiyu Chen; Fuguo Jia; Jincheng Zhang; Yanlong Han; Anqi Li; Yinglong Wang; Jiaming Fei; Shaohang Shen; Wenyu Feng; Xianzhi Hao (Biosystems Engineering, 2023)

Histone deacetylase CsHDA6 mediates the regulated formation of the anti-insect metabolite α-farnesene in tea (Camellia sinensis) - Shuhua Wu; Yuhua Yang; Jiaming Chen; Jianlong Li; Guotai Jian; Jie Yang; Kaiquan Mao; Lanting Zeng; Dachuan Gu (Plant Science, 2023)

Tentative exploration on water-promoted catalytic ozonation of Cl-VOCs and feasibility of application in complex flue gas over monolithic cobalt catalyst - Li Xiang; Luyang Zhang; Jiaming Shao; Fawei Lin; Zhihua Wang; Beibei Yan; Guanyi Chen (Journal of Hazardous Materials, 2023)

Fracture behavior investigation of self-compacting rubberized concrete by DIC and mesoscale modeling - Xing Li; Fuheng Ma; Xudong Chen; Jiang Hu; Jiaming Wang (Journal of Cleaner Production, 2023)

Numerical simulation approach for predicting rice milling performance under different convex rib helix angle based on discrete element method - Anqi Li; Fuguo Jia; Shaohang Shen; Yanlong Han; Peiyu Chen; Yinglong Wang; Jincheng Zhang; Wenyu Feng; Jiaming Fei; Xianzhi Hao (Innovative Food Science & Emerging Technologies, 2023)

Microbially driven fate of terrigenous particulate organic matter in oceans - Lianbao Zhang; Mingming Chen; Yue Zheng; Jianning Wang; Xilin Xiao; Xiaowei Chen; Chen Hu; Jiaming Shen; Jihua Liu; Kai Tang; Dapeng Xu; Qiang Shi; et al. (Limnology and Oceanography, 2023)
A long‐standing enigma in oceanography is why terrestrial organic matter is “missing” in the global ocean, despite the considerable discharge into it every year. Although some explanations, such as mineralogical composition, hydrodynamic processes, and priming effect, have been proposed, we hypothesize that the essential mechanism behind the missing organic matter is microbial processing, for which the underlying coupled geochemical, molecular, and genetic evidence is unknown. An ultra‐large‐volume, long‐term river–seawater stratified simulation system was constructed to unravel the microbially driven fate of terrigenous particulate organic matter (POM) in oceans. Analysis of combining the molecular with POM chemical composition data suggests that Bacteroidetes could act as pioneers in the processing of terrigenous POM in oceans, degrading high‐molecular‐weight, high‐carbon compounds such as polysaccharides. Remaining low‐molecular‐weight nitrogenous organic matter is subsequently degraded by Planctomycetes and Proteobacteria. Isotopic signals show that this preferential degradation causes a distinct “aging” effect of POM, and along with nitrification enhanced by remineralization, causes a decrease in the POM C : N ratio. Degradation of terrigenous POM and bacterial biomass biosynthesis leads to positive deviations in δ 15 N and δ 13 C. Relatively refractory hydrocarbons, aromatic compounds, and phenols are accumulated by microbial processes in this system. This study provides mechanistic insights into the missing chemical and isotopic signals and microbially driven fate of terrigenous POM in the ocean, with important implications for how riverine material input affects marine carbon and nitrogen cycling.

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Brain microstructural alterations in the left precuneus mediate the association between KIBRA polymorphism and working memory in healthy adults: a diffusion kurtosis imaging study - Junxia Wang; Sichu Wu; Yi Sun; Jiaming Lu; Jilei Zhang; Yu Fang; Zhao Qing; Xue Liang; Wen Zhang; Qian Chen; Xin Zhang; Bing Zhang (Brain Imaging and Behavior, 2022)
Kidney and brain expressed protein (KIBRA) rs17070145 is associated with working memory function and cognitive processes. However, the neural mechanisms underlying these associations are not fully understood. This study aimed to explore the effect of KIBRA polymorphism on brain microstructure and blood oxygenation level dependent (BOLD) fluctuations using diffusion kurtosis imaging (DKI) and resting-state functional magnetic resonance imaging (fMRI) in 163 young adults. We also investigated that whether the imaging alterations mediated the association between KIBRA gene and working memory performance. Voxel-based analysis of DKI data showed that KIBRA C-allele carriers exhibited increased axial diffusivity (AD), radial diffusivity (RD) and mean diffusivity (MD) as well as decreased fractional anisotropy (FA), mean kurtosis (MK) and radial kurtosis (RK) compared with KIBRA TT homozygotes, primarily involving the prefrontal lobe, left precuneus and the left superior parietal white matter. Meanwhile, KIBRA C-allele carriers exhibited decreased amplitude of low-frequency fluctuation (ALFF) in the left precuneus compared to KIBRA TT homozygotes. Mediation analysis revealed that the DKI metrics (MK and RK) of the left precuneus mediated the effect of the KIBRA polymorphism on working memory performance. Moreover, the MK and RK in the left precuneus were positively correlated with ALFF in the same brain region. These findings suggest that abnormal DKI parameters may provide a gene-brain-behavior pathway in which KIBRA rs17070145 affects working memory by modulating brain microstructure in the left precuneus. This illustrates that DKI may provide additional biological information and reveal new insights into the neural mechanisms of the KIBRA polymorphism.

Differential patterns and assembly processes of bacterial communities from distinct microhabitats in a subtropical estuary - Kang Ma; Ze Ren; Jiaming Ma; Nannan Chen; Jingling Liu (Frontiers in Marine Science, 2022)
Estuarine ecosystems interconnect freshwater and marine environments, and comprise multiple highly dynamic and complex microhabitats. The resident microbiota in estuary is influenced by contrasting microenvironmental heterogeneity. However, the bacterial patterns and assembly processes in different microhabitats of estuarine ecosystem are not well studied. Here, we investigated the bacterial diversity, functions and community assembly mechanisms of mangrove soil, river sediment and overlying water in a subtropical estuary. Results showed that similar profiles of bacterial communities existed in the mangrove soil and river sediment and were dominated by Proteobacteria, Bacteroidetes and Acidobacteria. In terms of different microhabitats, the lowest alpha diversity of bacterial communities was found in overlying water and were dominated by Proteobacteria, Actinobacteria and Bacteroidetes. Meanwhile, the functional potential genes associated with carbon metabolisms were also substantially different in the three microhabitats. The relative abundance of genes connected to aerobic carbon respiration was significantly higher in overlying water than in the other two microhabitats. Bacterial communities in river sediments were enriched for genes associated with aerobic methane oxidation. The strong environmental heterogeneity of the three nearby microhabitats shaped the taxonomic and functional composition of the bacterial communities in estuarine ecosystem. Moreover, the plant rhizosphere effect increased the proportion of the dispersal limitation processes in mangrove soils compared to that in river sediments, while the overlying water was fluid and had less environmental selection processes compared to that in mangrove soil and river sediment. The bacterial communities in river sediment construct a more clustered network, while the overlying water network showed the highest complexity. Our findings reveal the differences of bacterial patterns and community assembly mechanisms in distinct microhabitats of estuarine ecosystems, and provide important insights for a comprehensive understanding of the mechanisms to maintain estuarine wetland conservation under environmental changes.

Simulations of sea fog case impacted by air–sea interaction over South China Sea - Liguo Han; Shuqin Zhang; Feng Xu; Jingjing Lü; Zebin Lu; Guiling Ye; Siqi Chen; Jianjun Xu; Jiaming Du (Frontiers in Marine Science, 2022)
A sea fog event in the South China Sea was simulated using a coupled ocean–atmosphere model (WRF for the atmosphere and ROMS for the ocean). Offshore and onshore visibility, liquid water content, air temperature, humidity, and wind speed observations and MICAPS data were utilized to validate the model results. The results of the coupled model were also compared with those of the uncoupled atmosphere model. Sea fog duration in the coupled model was closer to offshore and onshore observations, but the uncoupled model emptily forecasted offshore fog, and underreported onshore fog. Air–sea temperature difference played an important role in regulating the formation and dissipation of sea fog. The decrease of sea surface temperature in the coupled model cooled the low-level atmosphere, promoted the condensation of low-level water vapor, and increased the low-level water vapor. The decrease of air–sea temperature difference strengthened the low-level stable stratification, which weakened the horizontal wind speed and favored the formation and development of sea fog. Rising wind speed was the major driver of fog dissipation.

Occurrence and driving forces of different nitrogen forms in the sediments of the grass and algae-type zones of Taihu Lake - Zihan Zhao; Mingli Zhang; Jiaming Tian; Kangkang Yu; Yan Chen; Yanhua Wang (Environmental Science and Pollution Research, 2022)

Genome-wide genetic diversity and IBD analysis reveals historic dissemination routes of pear in China - Xuening Chen; Mingyue Zhang; Manyi Sun; Yueyuan Liu; Shengnan Li; Bobo Song; Mengyan Li; Shaoling Zhang; Runze Wang; Jiaming Li; Kejiao Zhao; Jun Wu (Tree Genetics & Genomes, 2022)

Phosphorylation of CRMP2 by Cdk5 Negatively Regulates the Surface Delivery and Synaptic Function of AMPA Receptors - Longfei Cheng; Keen Chen; Jiong Li; Jiaming Wu; Jiaqi Zhang; Li Chen; Guoqing Guo; Jifeng Zhang (Molecular Neurobiology, 2022)

Tilt deformation and instability of the slope for predicting rainfall-induced landslide - Handong Liu; Jing-jing Liu; Jiaxing Chen; Jiaming Luo; Wei Guo (Arabian Journal of Geosciences, 2022)

NoiD, a DedA membrane protein required for homeostasis maintaining of Rhizobium leguminosarum biovar viciae during symbiosis with Pisum sativum - Xiaofang Li; Jiaming Xu; Yajuan Wei; Zirui Chen (Symbiosis, 2022)

Human Bone Marrow Mesenchymal Stem Cell–Derived Exosomes Attenuate Blood–Spinal Cord Barrier Disruption via the TIMP2/MMP Pathway After Acute Spinal Cord Injury - Wang Xin; Shi Qiang; Ding Jianing; Liang Jiaming; Lin Fangqi; Cai Bin; Chen Yuanyuan; Zhang Guowang; Xu Jianguang; Lian Xiaofeng (Molecular Neurobiology, 2021)

Altered resting-state networks may explain the executive impairment in young health immigrants into high-altitude area - Xiaoming Chen; Jian Liu; Jiye Wang; Zhenlong Xin; Qian Zhang; Wenbin Zhang; Yibin Xi; Yuanqiang Zhu; Chen Li; Jiaming Li; Yuedong Han; Jie Liu; et al. (Brain Imaging and Behavior, 2021)

Double decomposition and optimal combination ensemble learning approach for interval-valued AQI forecasting using streaming data - Zicheng Wang; Liren Chen; Jiaming Zhu; Huayou Chen; Hongjun Yuan (Environmental Science and Pollution Research, 2020)

A novel facial attractiveness evaluation system based on face shape, facial structure features and skin - Jian Zhao; Miao Zhang; Chen He; Xie Xie; Jiaming Li (Cognitive Neurodynamics, 2020)

Development and characterization of 33 SNP markers for the red-crowned crane (Grus japonensis) using a genotyping-by-sequencing approach - Nan Xu; Yining Chen; Jiaming Zhang; Qingzheng Zhang; Jing Yang; Jingjing Li; Hongyi Liu (Conservation Genetics Resources, 2020)

Influences of ABC transporter and CYP3A4/5 genetic polymorphisms on the pharmacokinetics of lenvatinib in Chinese healthy subjects - Jiaming Li; Xiaoqian Wang; Chen Ning; Zhaoyu Wang; Yao Wang; Ming Zheng; Siliang Zhang; Yang Lu; Yongjie Zhang; Ning Li; Xijing Chen; Di Zhao (European Journal of Clinical Pharmacology, 2020)

CDKN1B Mediates Apoptosis of Neuronal Cells and Inflammation Induced by Oxyhemoglobin via miR-502-5p After Subarachnoid Hemorrhage - Dong Chen; Xianwei Wang; Jiaming Huang; Sifu Cui; Liqiang Zhang (Journal of Molecular Neuroscience, 2020)

Dynamic Analysis of the Rock Burst Potential of a Longwall Panel Intersecting with a Fault - Lishuai Jiang; Peng Kong; Peipeng Zhang; Jiaming Shu; Qingbiao Wang; Lianjun Chen; Quanlin Wu (Rock Mechanics and Rock Engineering, 2020)

Low genetic differentiation among altitudes in wild Camellia oleifera, a subtropical evergreen hexaploid plant - Xiaomao Huang; Jiaming Chen; Xiaoqiang Yang; Shihua Duan; Chuan Long; Gang Ge; Jun Rong (Tree Genetics & Genomes, 2018)

An efficient method for developing polymorphic microsatellite markers from high-throughput transcriptome sequencing: a case study of hexaploid oil-tea camellia (Camellia oleifera) - Xiangyan Cui; Xiaomao Huang; Jiaming Chen; Xiaoqiang Yang; Jun Rong (Euphytica, 2018)

Study of physico-mechanical properties of Emeishan basalt saprolites in Yunnan, China - Zhe Ren; Luyue Zhang; Zemin Xu; Jiaming Zhang; Jipu Chen (Bulletin of Engineering Geology and the Environment, 2017)

Chemical and isotopic constrains on the origin of brine and saline groundwater in Hetao plain, Inner Mongolia - Jun Liu; Zongyu Chen; Lijuan Wang; Yilong Zhang; Zhenghong Li; Jiaming Xu; Yurong Peng (Environmental Science and Pollution Research, 2016)

A spatial-temporal analysis of urban recreational business districts: A case study in Beijing, China - He Zhu; Jiaming Liu; Chen Chen; Jing Lin; Hui Tao (Journal of Geographical Sciences, 2015)

Industrial spatial agglomeration using distance-based approach in Beijing, China - Jiaming Li; Wenzhong Zhang; Jianhui Yu; Hongxia Chen (Chinese Geographical Science, 2015)

Synergistic effect of EMS1-shRNA and sorafenib on proliferation, migration, invasion and endocytosis of SMMC-7721 - Jiaming Zhou; Li Chen; Yixin Zhang; Yuanyuan Wu; Guilan Wang; Song He; Zhongying Guo; Yingze Wei (Journal of Molecular Histology, 2014)

AtRabD2b, a Functional Ortholog of the Yeast Ypt1, Controls Various Growth and Developmental Processes in Arabidopsis - Fang Wang; Chao Liu; Chen Wei; Yuhai Cui; Qian Zheng; Jiaming Zhang; Jiangsheng Wu; Kede Liu (Plant Molecular Biology Reporter, 2012)

Production of cyclic adenosine monophosphate by Arthrobacter sp. A302 using fed-batch fermentation with pH-shift control - Jiaming Cao; Xiaochun Chen; Huajing Ren; Jindan Zhang; Lei Li; Yong Chen; Jian Xiong; Jianxin Bai; Hanjie Ying (World Journal of Microbiology and Biotechnology, 2012)

Dynamic mathematical models of batch experiments and fed-batch cultures for cyclic adenosine monophosphate production by Arthrobacter A302 - Lei Li; Xiaochun Chen; Huajing Ren; Jiaming Cao; Jian Xiong; Jianxin Bai; Hanjie Ying (World Journal of Microbiology and Biotechnology, 2011)

Factors of spatial distribution of recreation areas in peri-urban Beijing - Jiaming Liu; Run Wang; Tian Chen (Journal of Geographical Sciences, 2010)

Isolation and characterization of a novel EAR-motif-containing gene GmERF4 from soybean (Glycine max L.) - Gaiyun Zhang; Ming Chen; Xueping Chen; Zhaoshi Xu; Liancheng Li; Jiaming Guo; Youzhi Ma (Molecular Biology Reports, 2010)

Comparative analysis of distinct non-coding characteristics potentially contributing to the divergence of human tissue-specific genes - Qianli Huang; Jiaming Guo; Qq Ge; Jesse Li-Ling; Xueping Chen; Fei Ma (Genetica, 2009)